Analisis Perbandingan Kinerja Keuangan PT Telkom Indonesia (Persero) Tbk dan PT XLSMART Telecom Sejahtera Tbk Tahun 2022-2024 - Yohanes Kevin Lukna; Dona Olivia Sihombing; Talitha Nabila; Nabila Rahmadayanti; Fitri Yani Panggabean (CV. ITTC INDONESIA, 2025)
This study aims to analyze the comparison of financial performance between PT Telkom Indonesia (Persero) Tbk and PT XLSMART Telecom Sejahtera Tbk to understand the extent of the financial capabilities of these two telecommunications sector companies in the face of ongoing changes and intense competition. In the study, the analysis was conducted using financial ratios including liquidity (CR & QR), profitability (ROA & ROE), leverage (DAR & DER), and activity (TATO & FATO) using information from the company's financial statements in 2022 - 2024. The research findings show that both Telkom and XLSMART have values that are not yet classified as good in liquidity, profitability, and activity ratios. Of the three aspects, Telkom has an advantage in both liquidity ratios by 70%, both profitability ratios by 100%, and TATO by 35%. Meanwhile, XLSMART has the advantage of FATO by 45%. In terms of Leverage, Telkom has a ratio value that is classified as good, while XLSMART has not. Telkom has an advantage of 40% (DAR) and 95% (DER).